Rangkaian Sumber Informasi di Perpustakaan Sebagai Sarana Penelusuran Pendidikan Interaktif - Indah Purwani (Media Pustakawan, 2008)
This paper describes about the connection of information sources to education. This project will enhance the learning process and support to the education sector in Indonesia. The mission of this project is to socialize (enculture) the knowledge to education community and to build infrastructure of information technology in Indonesia.